MEMBANGUN APLIKASI AGENDA HARIAN GURU BERBASIS ANDROID (STUDI KASUS DI SMP BHAKTI MULYA BANJARAN - Iyus Muslimin S.T., M.T; Heri Sopian (Program Studi Teknik Informatika FTI UNIBBA, 2019)
Teacher’s daily agenda is an agenda that the teachers should be brought and filled by all the teachers when they will have a class, the teacher’s daily agenda contents all the teacher activities when they want to teach the students such as when they want to give materials to the students. The form is contents of; day, date, month, year, time and also the time of meeting, Competence standard, base competence indicator or the essential materials, descriptin of materials, percentage of the student of result, conclution and follow up. This activity is very important to do by all the teachers, especially to indicate the process of the teaching between the teachers and the students. As the writer know to do this activity almost the teachers are still manually or using hand writen and this less efectively and eficiency. Base on the case above the writer has an idea to make and to help easier and more efectively by making a program that called “Android Base of Application” this aplication can be as an input for all the teachers activities. The methodology used in this aplicatioan is waterfall methode. The laguage programs the writer using XML, Java and PHP. This program or is used to save the datas, base data using mysql and tools that is used android studios, Notepad ++, Mozilla firefox and xampp. By supporting internet connection in school center of SMP Bhakti Mulya Banjaran internet, this application is planned for the next will be used to input and procces of the teacher’s daily agendas. It will be divided into two parts that is android applicatioan and adminitrator. The android application will be used by users (the teachers) to input of the teachers daily agenda that is input by the user throught out by school web. Using the teacher application daily agenda base on android application is hoped will be helped to make easier all te teachers activity specially to make the teacher daily agenda in the classroom and also can be easier for the administrator to do it and to make the school reporting more quickly.